2003
DOI: 10.1017/s0033291703008146
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of co-morbidity in male suicide completers

Abstract: Suicide completers can be divided into at least three subgroups according to co-morbidity: a low co-morbidity group, a substance-dependent group and a group exhibiting childhood onset of psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 24 publications
(21 reference statements)
6
72
2
1
Order By: Relevance
“…Depression and associated feelings of hopelessness have been correlated to suicide attempts in both schizophrenia and affective psychoses. Hopelessness, substance abuse, greater insight into illness, and higher cognitive function are associated with greater risk for suicidal behavior in chronic schizophrenia, with hopelessness being the principal predictor (Kim et al, 2003). A recent review also found that the most common correlates of suicidality in schizophrenia are depressive symptoms and the depressive syndrome, although severe psychotic and panic-like symptoms may contribute as well (Siris, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Depression and associated feelings of hopelessness have been correlated to suicide attempts in both schizophrenia and affective psychoses. Hopelessness, substance abuse, greater insight into illness, and higher cognitive function are associated with greater risk for suicidal behavior in chronic schizophrenia, with hopelessness being the principal predictor (Kim et al, 2003). A recent review also found that the most common correlates of suicidality in schizophrenia are depressive symptoms and the depressive syndrome, although severe psychotic and panic-like symptoms may contribute as well (Siris, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was previously described by our group. [15][16][17] Data were collected according to the needs assessment procedures as initially developed for people with severe mental illness, 18 and subsequently for people with common mental disorders coming from the community. 19 In the course of the latter study, interrater reliability of the methods was assessed, comparing assessment by 2 independent panels, and found satisfactory for most areas (for example, care for addiction disorders problems).…”
Section: Data Gatheringmentioning
confidence: 99%
“…Research conducted with Micronesia citizens indicates that familiarity with suicide leads to an acceptance of the act by peers, who become prone to reproduce it (Rubinstein, 1983). In addition, several other studies (e.g., Agerbo et al, 2002;Cheng, Chen, Chen, & Jenkins, 2000;Kim et al, 2003;Kuramoto et al, 2010;Qin, Agerbo, & Mortensen, 2002;Runeson & Asberg, 2003) have demonstrated that suicide survivors (suicide bereaved individuals)-''someone who experiences a high level of self-perceived psychological, physical, and=or social distress for a considerable length of time after exposure to the suicide of another person'' (Jordan & McIntosh, 2011a, p. 7)-often exhibit a higher risk for suicide than the general population.…”
mentioning
confidence: 96%
“…In clinical and nonclinical populations, extreme psychological distress has been considered a major risk factor for suicidal ideation (Rosenfeld, Breitbart, Krivo, & Chochinov, 2000) and psychological distress has been shown to make a large contribution to suicide behavior (e.g., Hirsch, Webb, & Jeglic, 2011;Kim et al, 2003;Lamis, Malone, Langhinrichsen-Rohling, & Elis, 2010;Martin, 1997;Overholser, Freheit, & DiFilippo, 1997;Youssef et al, 2004;Zayas, Hausmann-Stabile, & Kuhlberg, 2011). In the general population, suicidal ideation is related with psychiatric illness and depressive mood (Bae, Lee, Cho, Kim, Im, & Cho, 2013) and several empirical studies linked depression, anxiety, and hostility with suicidal ideation (e.g., Campos, Besser, & Blatt, 2012, 2013Goldblatt, 2008;Lamis et al, 2010;Nepon, Belik, Bolton, & Sareen, 2010;Youssef et al, 2004).…”
mentioning
confidence: 99%